Avian architecture : how birds design, engineer & build - Goodfellow, Peter (Princeton University Press, 2011)
"Birds are the most consistently inventive builders, and their nests set the bar for functional design in nature. Avian Architecture describes how birds design, engineer, and build their nests, deconstructing all types of nests found around the world using architectural blueprints and detailed descriptions of the construction processes and engineering techniques birds use. This spectacularly illustrated book features 300 full-color images and more than 35 case studies that profile key species worldwide. Each chapter covers a different type of nest, from tunnel nests and mound nests to floating nests, hanging nests, woven nests, and even multiple-nest avian cities. Other kinds of avian construction--such as bowers and harvest wells--are also featured. Avian Architecture includes intricate step-by-step sequences, visual spreads on nest-building materials and methods, and insightful commentary by a leading expert"--Provided by publisher.